Capturing the Co-Benefits of Disaster Risk Management on the Private Sector Side - Rose, Adam (World Bank, Washington, DC, 2016)
In most countries, the private sector owns the vast majority of the buildings and a considerable portion of the infrastructure at risk. However, most investment in disaster risk management is made by the public sector, with the private sector lagging far behind. The situation represents missed opportunities for businesses to capture not only higher levels of the direct benefits of disaster risk management, but also a broader set of co-benefits to themselves and society as a whole. These co-benefits include ways of lowering production costs, improving the health of workers, and contributing to general economic stability. Ironically, many of these co-benefits are more tangible and immediate than ordinary disaster risk management benefits, which may not appear until a disaster has struck many years after the investment has been made. This study analyzes several important facets of private sector investment in disaster risk management, primarily from an economic perspective. It is intended as a first step toward promoting greater investment in disaster risk management by identifying potential co-benefits, explaining why they are not always pursued, and suggesting ways to integrate them into private sector decision-making. The latter includes government incentives, justified on the grounds that many private sector investments have extensive co-benefits, many of which pay dividends to society as a whole.